2019
DOI: 10.14710/reaktor.18.04.224-234
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Development of Edible Film/Coating from Lesser Yam Starch-Plasticizer Added with Potassium Sorbate or Cinnamon Oil in Affecting Characteristics and Shelf Life of Stored, Coated Strawberry

Abstract: Starch of lesser yam (‘gembili’ in Indonesian) has been used as a base for edible film and coating. Potassium sorbate and cinnamon oil are known as strong antimicrobial agents. This research was aimed to investigate the physical and mechanical characteristics of edible film from lesser yam starch-plasticizer formulations added with potassium (K) sorbate or cinnamon oil and its application as coating to strawberries. Incorporation of either K-sorbate or cinnamon oil at higher concentration resulted in reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…At room temperature, minimal weight loss was observed with 10 g papaya edible film (3.6 gm), and maximum weight loss was observed with 9 gm gelatin (5.76 gm). In general, the results show that weight loss can be reduced by adding various content to slow the penetration of water into the environment, where the content itself acts as a barrier to the edible surface [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…At room temperature, minimal weight loss was observed with 10 g papaya edible film (3.6 gm), and maximum weight loss was observed with 9 gm gelatin (5.76 gm). In general, the results show that weight loss can be reduced by adding various content to slow the penetration of water into the environment, where the content itself acts as a barrier to the edible surface [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…A smaller WVTR number indicates that water vapor will find it harder to pass through, extending the product's shelf life. Figure 10 shows that the value of WVTR tended to decrease as food color was added to the gelatin-based film that was made of cornstarch and gelatin [57]. The samples with yellow food color had the lowest WVTR value (73.21 g•m −2 •day −1 ).…”
Section: Barrier Effect On Filmmentioning
confidence: 99%
“…The antibacterial power of cinnamon essential oils has been tested in E. coli , Salmonella enterica , and Staphylococcus aureus (see Table 4; Pokatong & Decyree, 2019; Todd et al, 2013; Zhang et al, 2016), and is considerably effective against these pathogens, both in vivo and in vitro.…”
Section: Essential Oils Are Suitable Candidates For the Preservation ...mentioning
confidence: 99%
“…Lemon essential oils incorporated in a matrix slightly decreased the pH of strawberries after 14 days (control: 3.95 vs. lemon oil 3.7) (Perdones et al, 2012). However, several studies indicated no difference in the strawberries treated with cinnamon essential oil and the control, and the pH and concentration of citric acid did not vary significantly (Pokatong & Decyree, 2019; Tzortzakis, 2007). Cinnamon essential oil has been shown to slightly decrease the pH of guava fruit after 21 days of storage, with a pH of 4.05 versus 4.26 for the control (Etemadipoor et al, 2019).…”
Section: Essential Oils Are Suitable Candidates For the Preservation ...mentioning
confidence: 99%